ETIKA KELUARGA DALAM AGAMA TERHADAP JATI DIRI ANAK - Ahmad Taufik (El-Ghiroh : Jurnal Studi Keislaman, 2018)
In the view of Islam, since human birth has been conferred the potential of diversity. This potential is new in its simplest form, which is a tendency to submit and serve something. For this tendency to be submissive and devoted is not wrong, there needs to be external guidance. By nature the parents are the first mentors who are first known to the child. That is the importance of the influence of that guidance, to be associated with aqidah. The tendency to submit to something, may be directed to the wrong. Because even though every baby is born already has the potential for religion, the form of religious belief that the child will follow depends entirely on the guidance, care and influence of both parents.